Exposing Colonial and Imperial Roots in Neoliberal Globalization of BC K-12 International Education System - Lin, Gloria (Comparative and International Education / Éducation comparée et internationale, 2023)
With the rise of British Columbia (BC) kindergarten to Grade 12 (K–12) international education (formerly known as onshore schools) and the BC Offshore School Program, the business of international students is no longer limited to higher education. Working from a decolonizing framework, this study argues that the ever-changing, complex global system of international education in the context of BC’s public education system is a continuing form of imperialism and colonialism working under the guise of neoliberal globalization and the knowledge-based economy. Through a critical review of the current development of BC public schools’ K–12 international education, this study investigates how the shift from public schools dependent on shrinking government expenditure to relying on market-driven funding mechanisms has enormous implications on the way we think about education and the values that underpin educational endeavours.